Subterranean infrastructures in a sinking city: the politics of visibility in Jakarta. Issue 3 (2nd July 2020) - Colven, Emma
ABSTRACT: Indonesia's capital city of Jakarta is one of the world's fastest sinking cities. Land subsidence, primarily caused by excessive groundwater extraction, damages infrastructure and buildings, and contributes to worsened flood events and tidal inundation. Land subsidence was first identified as an issue in 1989, yet groundwater extraction has only recently been regulated. Meanwhile, city authorities have focused on implementing large-scale infrastructural interventions to reduce the impacts of flooding. This article analyzes why land subsidence remained unaddressed for so long. To do so, it explores the politics of infrastructure in Jakarta through the lens of in/visibility. Scholarship in infrastructure studies has tended to categorize infrastructure as either hyper-visible by design, or invisible until breakdown. This study extends theoretical engagements with infrastructure by examining how visibility, aesthetics, and materiality converge to shape urban and water governance in Jakarta in fundamental ways. Spectacular, visible infrastructures generate public and political attention, while below ground, hidden and invisible infrastructures are overlooked and politically unpopular to address. This "politics of visibility" articulates with a mode of aesthetic governmentality with uneven consequences for Jakarta's residents.